The impact of ESG regulatory announcements on stock returns : An event study of European Firms across different industries - Kastner, Miriam Josephine; Tyll, Ladislav; Bruder Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis applies event study methodology to explore the impact of ESG legislation concerning stock prices in the European Union using the Non-Financial Reporting Directive (NFRD) of 2014 as example. It considers two different events, the news on the publishing of the directive, April 15, 2014, and the actual publishing date, October 22, 2014. The study evaluates differences in stock price reactions around both dates. The dataset encompasses 203 companies across 17 EU countries. These companies represent 21 sectors and have actual MSCI ESG scores between AAA and B. To calculate abnormal returns, both the market-adjusted model and market model according to (Brown & Warner, 1985) are applied. Overall results show positive investor reaction post legislation announcement. However, on a more granular level mixed reactions were noticeable varying by country, sector and MSCI ESG score.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses